Macroeconomic Determinants of Remittances : Evidence from India - Gupta, Poonam (Washington, D.C. : International Monetary Fund, 2005)
Remittances to India have been growing rapidly since 1991, making it one of the largest recipients of remittances. This paper analyzes the determinants of remittances to India and finds that their growth over time can be explained by the increase in migration and total earnings of the migrants. Remittances are also affected by the economic environment in source countries, and appear to be countercyclical-that is, higher during periods of low economic growth in India. None of the remaining economic or political variables considered in the paper, including political uncertainty, interest rates, or exchange rate depreciation, are found to affect remittances significantly.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet